PREDICTING THE STRUCTURAL PERFORMANCE OF SANDWICH CONCRETE PANELS SUBJECTED TO BLAST LOAD CONSIDERING DYNAMIC INCREASE FACTOR - Hanifehzadeh, Mohammad; Mousavi, Mir Mohammad Reza (Journal of Civil Engineering, Science and Technology, 2019)
The safety of civil structures can be significantly improved against shock waves and blast loads by using steel concrete steel (SCS) protective walls. A numerical study was performed to simulate the response of SCS wall subjected to a near-field blast load. A conventional SCS panel subjected to near-field blast load and its structural performance had been evaluated in terms of maximum damage and deformation. The simulations were performed using ABAQUSfinite element package and built-in concrete damage plasticity concrete constitutive formulation. The dynamic increase factor (DIF) was added to the material constitutive behaviour to consider the rate effect on the behaviour of concrete and steel. The maximum deformation, the plastic strain, and the failure mode under different loading scenarios were investigated. This study predicts the structural response of the SCS panel with different blast charge and identification of optimum configuration in terms of concrete strength and plate thickness. In the second part of the study, two novel sandwich configurations consisting of a corrugated metal sheet and the concrete core are proposed and compared with the conventional protective walls. The optimum parameters for each structural component are identified using an optimization procedure. Based on this study, the proposed wall configuration shows more damage tolerance subjected to the blast loading as well as less out of plane deformation and weight compared to the conventional walls.